2019
DOI: 10.1111/ger.12446
|View full text |Cite
|
Sign up to set email alerts
|

Occlusal support is associated with nutritional improvement and recovery of physical function in patients recovering from hip fracture

Abstract: Objective This study aimed to elucidate the association between occlusal support and nutritional improvement and recovery of activities of daily living (ADLs) among elderly patients recovering from hip fracture. Background Many patients with hip fracture are malnourished, and malnutrition is associated with poor functional outcomes. Poor oral status is one reason for malnutrition because loss of occlusal support leads to masticatory disorders and can cause nutrient deficiencies. Methods We evaluated 202 elderl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…Tooth loss is associated with an accelerated decline in walking speed in older adults (57). Occlusal support is associated with improved nutrition, dysphagia, and ADL recovery in patients recovering from hip fractures (58) and among older adults needing long-term care (59). Improving occlusion by wearing an occlusal splint improves trunk balance and lower extremity muscle strength (60).…”
Section: Oral Status and Rehabilitation Outcomesmentioning
confidence: 99%
“…Tooth loss is associated with an accelerated decline in walking speed in older adults (57). Occlusal support is associated with improved nutrition, dysphagia, and ADL recovery in patients recovering from hip fractures (58) and among older adults needing long-term care (59). Improving occlusion by wearing an occlusal splint improves trunk balance and lower extremity muscle strength (60).…”
Section: Oral Status and Rehabilitation Outcomesmentioning
confidence: 99%
“…Several studies demonstrated the direct effect of oral functions on physical condition [ 37 , 38 ]. Above all, the effect of occlusal support on physical condition has been reported [ 27 , 28 , 29 , 30 , 31 , 32 ]. However, these studies were conducted as observational studies.…”
Section: Discussionmentioning
confidence: 99%
“…This suggestion may imply that rehabilitation of occlusal support has a positive effect on the prevention of accidental falls through the rehabilitation of mastication and nutritional status. Recent observational studies also demonstrated the association between occlusal support and physical function [ 27 , 28 , 29 , 30 , 31 , 32 ]. However, comparative studies that evaluate the effect of occlusal support and its rehabilitation on physical functions are still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the crude OR of sarcopenia for dysphagia (both dichotomised variables) was reported as being 6.17 [47]. Additionally, occlusal support (an indicator of oral function) showed 4.00 of OR for nutritional improvement [48].…”
Section: Potentially Associated Factors Of the Co-msmentioning
confidence: 99%